KAJIAN LITERATUR : FAKTOR YANG BANYAK MEMPENGARUHI OPINI AUDIT GOING CONCERN DENGAN MENGGUNAKAN METODE SLR (SYSTEMATIC LITERATURE REVIEW) TAHUN 2020-2023 - Roberto Josua F.Hasibuan; Carmel Meiden (Juremi: Jurnal Riset Ekonomi, 2024)
This research aims to summarize the results of previous research and provide a reference for future researchers to expand the independent variables by adding relevant moderating variables to be used in assessing their influence on the Going concern Audit Opinion (GCOA). An audit opinion is an important and useful thing for a company that can be used as a consideration for creditors or investors when lending a sum of money or making an investment. Researchers used a systematic literature review (SLR) methodology approach with a selected sample of 20 journals published for the period 2020 to 2023. The results of the research show that the factors that have a significant influence on going concern audit opinion are profitability, previous year's audit opinion, liquidity, debt default, solvency , financial distress, audit delay, Risk litigation